Versorgungsstrategie von Nervenverletzungen bei schwerem Weichteilschaden: Konsensus-Statement der Deutschsprachigen Arbeitsgemeinschaft für Mikrochirurgie der peripheren Nerven und Gefäße = Strategies on the treatment of nerve injuries accompanied by severe soft tissue damage - Harhaus-Wähner, Leila; Hirche, Christoph; Kneser, Ulrich (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2017)
Nerve injuries with severe soft tissue damage are rare and demand a complex and individualized treatment approach, in order to limit medical and socioeconomic consequences. Since uniform systematic evidence so far is lacking, inconsistent therapy standards are implemented depending on individual experiences and background of respective microsurgeons.
Publikationsdatum: 22. Juni 2017(online)
Gesehen am 09.08.2018